2021
DOI: 10.2215/cjn.15020920
|View full text |Cite
|
Sign up to set email alerts
|

Digital Applications Targeting Medication Safety in Ambulatory High-Risk CKD Patients

Abstract: Background and objectives Patients with CKD are at risk for adverse drug reactions, but effective community-based preventive programs remain elusive. In this study, we compared the effectiveness of two digital applications designed to improve outpatient medication safety. Design, setting, participants, & measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Ong et al showed that using mobile phone applica- tions prevents the progression of symptoms of a person's disease and improves their awareness of taking medicines, precautions, and possible side effects. On the other hand, these applications significantly reduce medication errors and help patients to comply more effectively with the treatment (46). Following the findings of these studies, training interventions can improve patients' awareness of the disease, symptoms, and treatment adherence.…”
Section: Discussionmentioning
confidence: 93%
“…Ong et al showed that using mobile phone applica- tions prevents the progression of symptoms of a person's disease and improves their awareness of taking medicines, precautions, and possible side effects. On the other hand, these applications significantly reduce medication errors and help patients to comply more effectively with the treatment (46). Following the findings of these studies, training interventions can improve patients' awareness of the disease, symptoms, and treatment adherence.…”
Section: Discussionmentioning
confidence: 93%
“…Stephanie et al. [ 48 ] evaluated a community-based digital intervention involving both patient and clinician and found the 1-year implementation largely reduced the rate and severity of medication discrepancies (proximal cause of medical errors) in high-risk CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, findings of the environmental scan indicated that patients should be leveraged to more actively participate in collection and maintenance of their own medication records as a possible change idea. In a cohort of patients with chronic kidney disease, Ong et al previously trialled the utilisation of a smartphone-based app to prompt patients to undertake a monthly medication review and report changes, additions or problems to their clinicians for reconciliation and early intervention which was associated with high uptake and a significant reduction in the number and severity of medication discrepancies 30. However, feedback from nurses involved in collecting BPMHs at our centre demonstrated that patients often did not understand the importance of having an up-to-date medication list, did not know what their role should be in creating and maintaining it and/or did not know that clinicians did not have access a centralised list of medications that had been prescribed to them across multiple providers or organisations.…”
Section: Discussionmentioning
confidence: 99%